2020
DOI: 10.1007/s00415-020-10031-1
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine formulation may influence subcutaneous complications from continuous subcutaneous apomorphine infusion in Parkinson’s disease

Abstract: Continuous subcutaneous (s.c.) apomorphine infusion is an effective therapy for Parkinson’s disease (PD), but a limitation is the formation of troublesome s.c. nodules. Various chemically non-identical apomorphine formulations are available. Anecdotal experiences have suggested that shifting from one of these (Apo-Go PumpFill®; apoGPF) to another (Apomorphine PharmSwed®; apoPS) may influence the occurrence and severity of s.c. nodules. We, therefore, followed 15 people with advanced PD (median PD-duration, 15 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1 18,22,24–26,29,52–71 . In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1 18,22,24–26,29,52–71 . In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS).…”
Section: Resultsmentioning
confidence: 99%
“…Common published adverse events of CSAI in major case series and case reports are listed in Table 4 and Table S1. 18,22,[24][25][26]29,[52][53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71] In an audit on reasons for discontinuing therapy of 107 patients over 10 years, Tyne et al 18 reported that therapy was discontinued in 16% of patients (with some opting for intermittent injections, and 10 going on to DBS). Although nine patients died during the audit periods, none of the deaths were attributed to CSAI.…”
Section: Causes For Discontinuation and Adverse Events Of Csaimentioning
confidence: 99%
“…The purpose of this study is to develop a novel formulation that combines these two drugs to increase their therapeutic potential. The formulation will be evaluated for its neuroprotective and pharmacokinetic properties in a rat model of Parkinson's disease [2,3].…”
Section: Introductionmentioning
confidence: 99%